PREFERENSI ATLET OKU SELATAN TERHADAP CITA RASA OLAHAN IKAN MUJAIR DENGAN METODE C-SAT (CUSTOMER SATISFICATION) - Melati Pratama (JURNAL PERIKANAN TROPIS, 2020)
Tilapia is one of the fresh water fish, and one of commodites that was cultivated by OKU Selatan specialy Ranau lake. Around the Ranau lake, tilapia usually was processed to grilled tilapia fish, turmeric seasoning, pindang Palembang and fried fish. The tilapia products had off-falvour so OKU Selatan athete ate other food like fried rice, fried chicken and tempeh, soto, instan noodles and etc. The aims for this research was to identified preference of OKU Selatan athlete to tilapia product, and analyzied flavor preference of OKU Selatan athlete based on five senses and cooking method. The data was calculated by C-Sat (Customer Satisfication). The results showed that the highest preference of OKU Selatan athelete to tilapia product at grilled tilapia such as 6.4 point and the lowest preference at Pindang such as 4.8 point. The highest preference of OKU Selatan to sensation taste at umami such as 9.9 point and the lowest at the bitter taste such as 1.5 point. The highest prefence of OKU Selatan to tilapia taste due processing at fried tilapia processed such as 9.8 point and the lowest at boiled tilapia processed such as 5.2 point. Athelete of OKU Selatan most prefer to tilapia that has umami sensation by fryied processed. Keywords : flavor, OKU Selatan athlete, tilapia product, C-Sat